Conduction mechanism of non-gold Ta/Si/Ti/Al/Ni/Ta ohmic contacts in AlGaN/GaN high-electron-mobility transistors - Li, Yang (2015)
This work investigates the conduction mechanism of non-gold Ta/Si/Ti/Al/Ni/Ta ohmic contact in un-doped AlGaN/GaN high-electron-mobility transistors (HEMTs) grown on Si. Temperature-dependent current–voltage (I–V) measurements reveal that the conduction occurs primarily via thermionic emission (TE). The extracted mean barrier height (ΦB) values are 0.113 and 0.121 eV and the mean contact resistance (Rc) values are 0.24 and 0.28 Ω mm, for annealing temperatures of 850 and 900 °C, respectively. The low Rc is attributed to the formation of low work function TixSiy at the metal–semiconductor interface. The high-resolution transmission electron microscopy (HR-TEM) and energy-dispersive X-ray spectroscopy (EDX) analysis provide further structural evidence in support of the TE mechanism.